Analisis Tingkat Kepuasan Pengguna E-Learning Universitas Telkom Menggunakan Metode End-User Computing Satisfaction - Khansa' Nadhifah Rabbaniah Al Habsyi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The rapid development of information technology, especially due to the COVID-19 pandemic that has spread in the community, has shifted all activities to online media including lectures at Telkom University. The e-learning information system media used is CeLOE LMS where this system is intended to support most of the online lecture activities for students during distance learning. The use of the CeLOE LMS has changed a lot from the beginning of online lectures until now, but the management of CeLOE LMS itself has never conducted research or evaluation related to satisfaction of using CeLOE LMS, it is necessary to have research related to this matter to assess the system implemented makes it easier for users according to their needs in terms of content, the accuracy of the information provided, ease of use, interface display, and timeliness in presenting the information. This research uses purposive sampling technique by distributing questionnaires through several social media platforms. The research model used is End-User Computing Satisfaction (EUCS) with 6 variables involved, namely Content, Accuracy, Format, Ease of Use, Timeliness, and End-User Satisfaction using calculation analysis PLS-SEM method with SmartPLS version 3.0 tools. The sample of this research consisted of 205 respondents of active students of Telkom University undergraduate study program with a total population of 22279 students. The results of the 5 proposed hypotheses, there are 2 hypotheses that are rejected because the results of t-statistics analysis >1,97 which means that the relationship between the Accuracy (ACC) variable and the Format (FOR) variable does not significantly effect the End-User Computing Satisfaction (EUS) variable.